Peter Larkin Duren 1935–2020: Peter Larkin Duren 1935–2020 - Osgood, Brad (Computational methods and function theory, 2025)
Photo courtesy of University of Michigan Photography Peter Larkin Duren was born in New Orleans, LA on April 30, 1935 and passed away at the age of 85 in Ann Arbor, MI on July 10, 2020. The Hp book still provides an illuminating treatment of the complex variables approach to the subject, the original approach, and is a natural companion to more recent books, e.g., the excellent book by P. Koosis [5], which includes Wolff’s proof of the Corona theorem. Writing in the American Mathematical Monthly Harold Boas, himself an award winning expositor and teacher, says “This volume is a valuable guidebook for tourists in the old country of analysis.